الصور البلاغية في مقامات الإلوري Rhetorical devices in al-Ilori’s maqamat (2024)
Despite the great impression of the Arabs and Non-Arabs writers to the art of Maqamat genre, invented by Badi’I Zaman Al-Hamadhani in the fourth century A.H., which gained a wide recognition in both Arabo-Islamic communities. The quantum values and importance added by this literary genre in to the Arabs’ literary heritage has made unique literary creative genre, which changes the status of Arabic prose writing, formulated in the form of funny stories, chosen a narrator named ‘Isa bn Hisham, and a vibrant Hero known: Abu -1- Fatih al-Iskandari. This unique style was later emulated by many Arabs’ writers by producing their own Maqamat, such as; Abu-L-Qazeem Muhammad Al- Hariri (d. 516 A.H), Zamakhshari (D.538 A.H.) Suyyuti (d. 1505 C.E). In the twenty-first century, the great gestures of Africa Arabic scholars in general, and Nigeria in particular, with this literary creativity is very impressive and applausive , with the production of different Maqamat, followed the styles of Badi’ Zaman al Hamadhani, Abu -1-Qasim al- Hariri and etc., amongst are: Dr. Abdul Bari Adetunji in his Maqamat titled : Kaswatu-L-‘Ary fi-1- Maqamat Abdul Bari, Mas’ud Abdul Ganiy Adebayo Al-Oyowiy, in his Maqamat, titled: Maqamat-1- Oyowy, Muhammad Awwal Abdul Salam popularly known as Sahibul -Qur’an Al-Ilory in his Maqamat, titled : Maqamat -Ilory, and Ahmad Tijani Yusuf Ajegunle popularly known as Riku-1 -Asifiyah in his Maqamat, titled : Maqamat Ibn Yusuf and etc. Despite the multiplicity of the studies contained in Al-Ilory’s Maqamat, the rhetorical features have not been studied, which has created a gap to fill by the researcher. Therefore, this research aims to study the rhetorical features in the Al-Ilory’s Maqamat. But, before delving in to the main discussion, the concept of Maqamat, its characteristics and elements would be discussed. Then a historical background of the author of Al-Ilory’s Maqamat would also be discussed.